Minimally invasive surgical technique for unstable supracondylar humerus fractures in children (Gartland type III or IV) - Lee, Chang-Hyun; Jung, Sung-Taek; Park, Chun-Gon; Kim, Joonyeong; Kang, Gyo Rim; Kim, Sungmin (Frontiers in Pediatrics, 2024)
Background: Achieving and maintaining anatomical reduction during the treatment of pediatric humerus fractures, classified as Gartland type III or IV, presents a clinical challenge. Herein, we present a minimally invasive surgical approach using a novel and simple K-wire push technique that aids in achieving and maintaining anatomical reduction.We reviewed data of children receiving treatment for supracondylar fractures of the humerus at our hospital between January 2016 and December 2020. Patients were divided into two groups based on the method of treatment: Group 1 was treated with the K-wire push technique, and Group 2 was treated with the standard technique as described by Rockwood and Wilkins. The medical records and radiographic images were reviewed. In total, 91 patients with Gartland types III and IV fractures were included, with 37 and 54 patients in Groups 1 and 2, respectively.The postoperative reduction radiographic parameters and Flynn scores at final follow-up were not significantly different between the two groups.The minimally invasive K-wire push technique for unstable supracondylar fractures in children is a safe and effective alternative for improving reduction. Using this technique, complications can be minimized, and the requirement for open reduction can be reduced.